2018
DOI: 10.1038/s41598-018-31161-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulating exopolysaccharide gene wcaF allows control of Escherichia coli biofilm formation

Abstract: While biofilms are known to cause problems in many areas of human health and the industry, biofilms are important in a number of engineering applications including wastewater management, bioremediation, and bioproduction of valuable chemicals. However, excessive biofilm growth remains a key challenge in the use of biofilms in these applications. As certain amount of biofilm growth is required for efficient use of biofilms, the ability to control and maintain biofilms at desired thickness is vital. To this end,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…However, we cannot rule out the possibility that a second acetylation takes place after formation of the oligosaccharide or polymer. The importance of WcaF is consistent with studies showing that this protein is critical to the formation of colanic acid in vivo and, more recently, the importance of that gene for biofilm formation. , We have also shown that WcaB, the other encoded acetyltransferase, had no influence on the disaccharide but enhances the ability of WcaA to add the fifth sugar to the CA repeating unit and also appears to be a critical protein in the assembly of the oligosaccharide repeat unit.…”
Section: Discussionsupporting
confidence: 89%
“…However, we cannot rule out the possibility that a second acetylation takes place after formation of the oligosaccharide or polymer. The importance of WcaF is consistent with studies showing that this protein is critical to the formation of colanic acid in vivo and, more recently, the importance of that gene for biofilm formation. , We have also shown that WcaB, the other encoded acetyltransferase, had no influence on the disaccharide but enhances the ability of WcaA to add the fifth sugar to the CA repeating unit and also appears to be a critical protein in the assembly of the oligosaccharide repeat unit.…”
Section: Discussionsupporting
confidence: 89%
“…Biofilm thickness was detected according to a previously published method, with minor modification [ 11 ]. After incubation, the microscope slides with biofilm from each group were gently rinsed with deionised water to remove unattached cells and then stained with SYTO9/propidium iodide according to the instructions of the L13152 LIVE/DEAD BacLight bacterial viability kit (Invitrogen Molecular Probes, USA).…”
Section: Methodsmentioning
confidence: 99%
“…CA production is not required for surface attachment, however, CA is critical for the formation of the complex three-dimensional structure and depth of E. coli biofilms [ 63 ]. Bacterial biofilms have been described as sessile bacterial communities that live attached to each other and stick onto surfaces [ 68 , 69 ]. Biofilm is so abundant in natural environments, but can also cause persistent, antibiotic-resistant infections [ 68 , 70 ], especially impinge significantly upon our industrialized world [ 71 , 72 ].…”
Section: Polysaccharides Of Lps Consume Lots Of Nutrients and Influenmentioning
confidence: 99%